Three arginine residues in apolipoprotein A-I are critical for activation of lecithin:cholesterol acyltransferase - Stein Roosbeek; Berlinda Vanloo; Nicolas Duverger; Hans Caster; Joke Breyne; Iris De Beun; Hetal Patel; Joël Vandekerckhove; Carol Shoulders; Maryvonne Rosseneu; Frank Peelman (Journal of Lipid Research, 2001)
Previous studies have suggested that the helical repeat formed by residues 143–164 of apolipoprotein A-I (apoA-I) contributes to lecithin:cholesterol acyltransferase (LCAT) activation. To identify specific polar residues involved in this process, we examined residue conservation and topology of apoA-I from all known species. We observed that the hydrophobic/hydrophilic interface of helix 143–164 contains a cluster of three strictly conserved arginine residues (R149, R153, and R160), and that these residues create the only significant positive electrostatic potential around apoA-I. To test the importance of R149, R153, and R160 in LCAT activation, we generated a series of mutant proteins. These had fluorescence emission, secondary structure, and lipid-binding properties comparable to those of wild-type apoA-I. Mutation of conserved residues R149, R153, and R160 drastically decreased LCAT activity on lipidprotein complexes, whereas control mutations (E146Q, D150N, D157N, R171Q, and A175R) did not decrease LCAT activity by more than 55%. The markedly decreased activities of mutants R149, R153, and R160 resulted from a decrease in the maximal reaction velocity Vmax because the apparent Michaelis-Menten constant Km values were similar for the mutant and wild-type apoA-I proteins. These data suggest that R149, R153, and R160 participate in apoA-I-mediated activation of LCAT, and support the “belt” model for discoidal rHDL. In this model, residues R149, R153, and R160 do not form salt bridges with the antiparallel apoA-I monomer, but instead are pointing toward the surface of the disc, enabling interactions with LCAT.—Roosbeek, S., B. Vanloo, N. Duverger, H. Caster, J. Breyne, I. De Beun, H. Patel, J. Vandekerckhove, C. Shoulders, M. Rosseneu, and F. Peelman. Three arginine residues in apolipoportein A-I are critical for activation of lecithin:cholesterol acyltransferase J. Lipid Res. 2001. 42: 31–40.